2011
DOI: 10.1007/s10194-011-0354-0
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic damage to the mandibular nerves as assessed by the masseter inhibitory reflex

Abstract: Iatrogenic injury of the inferior alveolar or lingual nerves frequently leads to legal actions for damage and compensation for personal suffering. The masseter inhibitory reflex (MIR) is the most used neurophysiological tool for the functional assessment of the trigeminal mandibular division. Aiming at measuring the MIR sensitivity and specificity, we recorded this reflex after mental and tongue stimulations in a controlled, blinded study in 160 consecutive patients with sensory disturbances following dental p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…According to most studies, jaw-closing muscle SP1 and SP2 were elicited by activation of similar afferent fibers in the 2nd and 3rd division of the trigeminal nerve [4,10,17]. SP1 and SP2 are produced by activation of brainstem interneurons which inhibit the motorneurons of jaw-closing muscles, with SP1 via an oligosynaptic, SP2 via a polysynaptic neural net [5,10].…”
Section: Excitability Of the Brainstem Networkmentioning
confidence: 99%
“…According to most studies, jaw-closing muscle SP1 and SP2 were elicited by activation of similar afferent fibers in the 2nd and 3rd division of the trigeminal nerve [4,10,17]. SP1 and SP2 are produced by activation of brainstem interneurons which inhibit the motorneurons of jaw-closing muscles, with SP1 via an oligosynaptic, SP2 via a polysynaptic neural net [5,10].…”
Section: Excitability Of the Brainstem Networkmentioning
confidence: 99%
“…A study conducted in June 2011 by Biasiotta et al [ 19 ] states that the masseter inhibitory reflex (MIR) test is the most used neurophysiological tool for the functional assessment of the trigeminal mandibular division. It consists of a reflex inhibition of the jaw-closing muscles elicited by peri- or intraoral electrical stimulations.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of a reflex inhibition of the jaw-closing muscles elicited by peri- or intraoral electrical stimulations. Their study revealed that MIR testing shows an almost absolute specificity (99%) and reliably demonstrates nerve damage beyond doubt, whereas the relatively low sensitivity (51%) makes the finding of a normal MIR by no means sufficient to exclude nerve damage [ 19 ]. In other words, this test principle is that abnormality does prove nerve damage, and normality does not disprove it.…”
Section: Introductionmentioning
confidence: 99%
“…Because MIR is mediated by non-nociceptive Ab fibers, MIR abnormalities are unrelated to pain. 9 To our knowledge, there are no works which quantify the entity of alveolar nerve impairment and demonstrate the suitability of surgical removal of the necrotic bone in order to improve alveolar nerve function in patients affected by BRONJ. The aim of our study was to determine and even possibly quantify the presence of alveolar nerve impairment in a patient affected by mandibular BRONJ before and after surgical removal of necrotic bone assessed by MIR.…”
Section: Postsurgical Improvement Of Inferior Alveolar Nerve In Bronjmentioning
confidence: 99%
“…The MIR was recorded according to the Recommendations of the IFCN. 12 To evaluate the diagnostic accuracy of MIR, we chose, as in Biasiotta's paper, 9 to measure only the early SP1 component. The short-latency response SP1 is far more accurate than the long-latency response SP2 because it is supplied by fewer reflex afferents.…”
Section: Clinical Casementioning
confidence: 99%